2023
DOI: 10.1590/1678-992x-2022-0093
|View full text |Cite
|
Sign up to set email alerts
|

The use of sugar beet pulp in pig diet to control skatole analysed by HPLC quantification method

Abstract: This study aimed to determine the efficacy of a finishing diet added with sugar beet pulp to reduce backfat skatole of entire male pigs, using the optimised high-performance liquid chromatographic (HPLC) method. The study comprised 72 males Pietrain (Large White × Landrace), divided into two groups of 36 animals each. Pigs in group A (treatment) were fed a supplemented formula (addition of 10 % beet pulp). while animals in group B (control) received a commercial feed, both for a period of 14 days before slaugh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…Skatole can be reabsorbed through a pig’s skin upon contact with fecal contamination, thus increasing the fat skatole levels when the animal is in contact with fecal and urine residues [ 77 ]. Multiple studies have identified skatole concentration levels in intact males ranging from 100 ng/g to 200 ng/g of liquid fat [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. In the present study, all values were lower than 80 ng/g, which might be attributed to the beet supplementation, a measure previously demonstrated to effectively reduce skatole levels [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skatole can be reabsorbed through a pig’s skin upon contact with fecal contamination, thus increasing the fat skatole levels when the animal is in contact with fecal and urine residues [ 77 ]. Multiple studies have identified skatole concentration levels in intact males ranging from 100 ng/g to 200 ng/g of liquid fat [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. In the present study, all values were lower than 80 ng/g, which might be attributed to the beet supplementation, a measure previously demonstrated to effectively reduce skatole levels [ 86 , 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have identified skatole concentration levels in intact males ranging from 100 ng/g to 200 ng/g of liquid fat [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. In the present study, all values were lower than 80 ng/g, which might be attributed to the beet supplementation, a measure previously demonstrated to effectively reduce skatole levels [ 86 , 87 ]. The carbohydrates provided to the animals throughout the year in the form of beet pulp have the capacity to alter the activity and composition of gut microflora.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation